Does volume of gold consumption influence the world gold price? - Maria Immanuvel S; Daniel Lazar (Journal of Risk and Financial Management, 2022)
Gold is a universal commodity traded across the world. The London Bullion Market Association (LBMA) fixes prices twice a day, known as AM and PM fix prices. This study is an attempt to find out whether the volume of gold consumption shows any significant impact on the world gold prices, known as LBMA fix prices. The sample includes major gold-consuming countries, such as India, the USA, China, Japan, and countries in Europe and the Middle East grouped together under Europe and the Middle East, respectively. The results conclude that there exists a long-run relationship between LBMA fix prices and the gold demand of all the countries. Furthermore, the volume of gold demand significantly influences LBMA AM fix and PM fix prices. It is found out that the demand of all the countries together, and India and China individually, affect the world gold prices significantly. India consistently stands as the largest consumer of gold in the world gold market. In spite of this, India is a price taker. Bullion associations and commodity exchanges that allow bullion trade in India may take initiatives to make India a price maker in the world gold markets.
Keywords: 650; cointegration; gold demand; impulse response function; price taker; variance decomposition; world gold market